Spray Deposition of Mechanically Alloyed F/M ODS Steel Powder - Kang, Suk Hoon; Rhee, Chang-Kyu; Noh, Sanghoon; Kim, Tae Kyu (Archives of Metallurgy and Materials, 2019)
Thermal/cold spray deposition were used for additive manufacture of oxide dispersion strengthened (ODS) steel layers. Mechanically alloyed F/M ODS steel powders (Fe(bal.)-10Cr-1Mo-0.25Ti-0.35Y2O3 in wt.%) were sprayed by a high velocity oxygen fuel (HVOF) and cold spray methods. HVOF, as a thermal method, was used for manufacturing a 1 mm-thick ODS steel layer with a ~95% density. The source to objective distance (SOD) and feeding rate were controlled to achieve sound manufacturing. Y2Ti2O7 nano-particles were preserved in the HVOF sprayed layer; however, unexpected Cr2O3 phases were frequently observed at the boundary area of the powders. A cold spray was used for manufacturing the Cr2O3-free layer and showed great feasibility. The density and yield of the cold spray were roughly 80% and 45%, respectively. The softening of ODS powders before the cold spray was conducted using a tube furnace of up to 1200°C. Microstructural characteristics of the cold sprayed layer were investigated by electron back-scattered diffraction (EBSD), the uniformity of deformation amount inside powders was observed.
Keywords: additive manufacture; mechanically alloyed ODS powder; HVOF; Cold spray